2012
DOI: 10.1097/rli.0b013e3182300fe4
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Contrast-Enhanced Computed Tomography Imaging Biomarkers Correlated With Immunohistochemistry for Monitoring the Effects of Sorafenib on Experimental Prostate Carcinomas

Abstract: Sorafenib significantly suppressed tumor perfusion, tumor vascularity, and PS quantified by DCE-CT in experimental prostate carcinomas in rats. These functional CT surrogate markers showed moderate correlations with antiangiogenic, antiproliferative, and proapoptotic effects observed by immunohistochemistry. DCE-CT may be applicable for the quantification of noninvasive imaging biomarkers of therapy response to antiangiogenic therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 45 publications
3
18
0
3
Order By: Relevance
“…Emerging functional and molecular imaging techniques using MR imaging, CT, US, positron emission tomography (PET), and optical-based technologies are being developed and have shown promising results for monitoring cancer more accurately than traditional morphologic imaging (11)(12)(13)(14)(15)(16)(17). Among these, CT is currently the most commonly used first-line imaging modality for staging and monitoring of diseases in oncology because of its wide availability and the availability of standardized CT protocols which yield reproducible imaging results.…”
Section: Accreditation and Designation Statementmentioning
confidence: 99%
“…Emerging functional and molecular imaging techniques using MR imaging, CT, US, positron emission tomography (PET), and optical-based technologies are being developed and have shown promising results for monitoring cancer more accurately than traditional morphologic imaging (11)(12)(13)(14)(15)(16)(17). Among these, CT is currently the most commonly used first-line imaging modality for staging and monitoring of diseases in oncology because of its wide availability and the availability of standardized CT protocols which yield reproducible imaging results.…”
Section: Accreditation and Designation Statementmentioning
confidence: 99%
“…9,10 Hence, the evolving therapeutic field of vascular-modulating drugs requires new noninvasive methods for assessing tumor vascularity in vivo. [11][12][13][14][15] In 1967, Milne 16 showed that lung tumors may have a dual blood supply by the pulmonary and the aortic system, with a trend toward histological type-specific circulatory pattern. The advent of CT perfusion (CTP) within the last decade allowed for a direct, noninvasive quantification of the vascular function.…”
Section: Results: According To Biopsy 37 Patients Had Nsclc (22 Adenmentioning
confidence: 99%
“…Besides, CTP imaging is performed much faster than MRI, its application is more convenient for the patient, and can easily be combined with an abdominal staging CT as part of the same Experimental work has also shown the usefulness of CTP for response assessment to radiotherapy and anti-angiogenic drugs. [14,15] One inherent drawback of CTP is the additional radiation burden delivered to the patient, requiring a well-considered weighing of potential benefits of cancer characterization. It should however be noted that the prostate-though being the most sensitive organ within the field -in any way will undergo organdestructive treatment, be it by radiotherapy or by prostatectomy.…”
Section: Discussionmentioning
confidence: 99%